PENGARUH TENAGA KERJA DAN TINGKAT OPTIMASI PENGGUNAAN TENAGA KERJA PADA USAHATANI NENAS LAHAN SKALA SEMPIT DAN SKALA LUAS DI KABUPATEN KAMPAR - Ridho Febriandi; Syaiful Hadi; Jumatri Yusri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research are analyze the effect of labor on production pineapple, analyze the level of optimization of the use of labor, and analyze the optimization of the use of labor between broad and narrow area of land in Kampar. The methods of analysis used in this study is regression analyze. Based on the result of the analysis of effect labor on production pineapple, the amount of labor significantly affect the amount of production of pineapples, it applies to farming in a narrow area, wide area, and also overall. labor is a factor of production is greatest effect on farm production pineapple research area. labor used in the farming of pineapple consists of labor within the family and outside the family labor, in which the activities carried out are weeding and harvesting.The use value of labor in the area showed that the use of labor is not optimal, it should be increasing the number of workers, in order to increase productivity. level optimization on large tracts of land is better than the narrow land, it demonstrates the use of labor on a large area is optimal from the narrow land. then to optimize the use of labor on a narrow piece of land is necessary to increase the amount of labor. keywords: pineapple production, labor, optimazation.